2021
DOI: 10.3390/antiox10081270
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Pro-Oxidant Iron with Deferoxamine as a Treatment for Ischemic Stroke: Safety and Optimal Dose Selection in a Randomized Clinical Trial

Abstract: A role of iron as a target to prevent stroke-induced neurodegeneration has been recently revisited due to new evidence showing that ferroptosis inhibitors are protective in experimental ischemic stroke and might be therapeutic in other neurodegenerative brain pathologies. Ferroptosis is a new form of programmed cell death attributed to an overwhelming lipidic peroxidation due to excessive free iron and reactive oxygen species (ROS). This study aims to evaluate the safety and tolerability and to explore the the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(34 citation statements)
references
References 54 publications
(77 reference statements)
1
33
0
Order By: Relevance
“…It was discovered by analyzing the human glioma genome that ferroptosis-related gene signature can be applied to low-grade glioma border localization and detection and predict glioma cell death and glioma patient progression [ 133 136 ]. DFO is effective in treating ischemic stroke in a randomized clinical trial [ 137 ]. These findings suggest that ferroptosis is a potential target for treatment for TBI.…”
Section: Discussionmentioning
confidence: 99%
“…It was discovered by analyzing the human glioma genome that ferroptosis-related gene signature can be applied to low-grade glioma border localization and detection and predict glioma cell death and glioma patient progression [ 133 136 ]. DFO is effective in treating ischemic stroke in a randomized clinical trial [ 137 ]. These findings suggest that ferroptosis is a potential target for treatment for TBI.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, administration of deferoxamine which chelates redox-active iron to inhibit ferroptosis has been shown to improve blood oxidative stress markers as an adjunctive therapy for patients with ST-segment elevation MI ( 142 ). Intravenous infusion of deferoxamine mesylate at the initiation of thrombolysis was also effective in ischemic stroke patients, with no apparent adverse effects ( 143 ). Therefore, pharmacological treatment to maintain iron homeostasis and inhibit ferroptosis may serve as a new therapeutic strategy for CVDs.…”
Section: Discussionmentioning
confidence: 99%
“…Deferoxamine is an inducer of HIF-1 and its mediated antioxidant effect may be related to the inhibition of the Fenton reaction by chelating Fe 2+ (180). Clinical trials conducted by Mònica et al confirmed the effectiveness and safety of desferrioxamine in the treatment of ischemic stroke (181).Neuroglobin protein (ngb1) is a member of the bead protein family and its initiation process is regulated by transcription factors, such as HIF-1 and VEGF (182). Animal experiments have demonstrated that sub-nanomolar concentrations of Ngb1 prevent ROS accumulation, reduced antioxidant enzymes, and reduced expression of apoptotic proteins in astrocytes after exposure to H 2 O 2 (183).…”
Section: Endogenous Antioxidantsmentioning
confidence: 99%